2022
DOI: 10.1186/s13018-021-02897-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study for the treatment of proximal humeral fracture through the medial approach

Abstract: Background The treatment of complex 3- and 4-part proximal humeral fractures has been controversial due to numerous postoperative complications. With the further study of medial support and blood supply of humeral head, new techniques and conception are developing. The study aims to illustrate the medial approach of the proximal humeral fracture through cadaver autopsy. Method Upper limbs from 19 cadavers have been dissected to expose the shoulder … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Several studies reported that the medial approach for proximal humerus fractures involved a risk of iatrogenic neurovascular injury, especially to the musculocutaneous nerve and posterior humeral circumflex artery. 35,36 The anterior brachial circumflex artery, an important blood supply to the humeral head, runs laterally along the inferior border of the subscapularis tendon directly. This can be at risk during the DP approach, especially if the anatomy is distorted by the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the medial approach for proximal humerus fractures involved a risk of iatrogenic neurovascular injury, especially to the musculocutaneous nerve and posterior humeral circumflex artery. 35,36 The anterior brachial circumflex artery, an important blood supply to the humeral head, runs laterally along the inferior border of the subscapularis tendon directly. This can be at risk during the DP approach, especially if the anatomy is distorted by the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Humeral offset (HO) and glenoidal offset (GO) parameters are important morphological parameters in diagnostics and in therapy for shoulder pathologies. Humeral head preserving surgery remains the current state-of-the-art surgery for younger patients in the case of a fracture [ 1 , 2 ]. Likewise, arthroplasty of the shoulder joint is increasingly gaining importance in the treatment of degenerative and traumatic shoulder pathologies, especially in older patients [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%